A K-Band VCO With AC-Shorted Transformer Tank for 76–81 GHz FMCW Radars - Weihu Wang; Brian A. Floyd (IEEE Access)
This paper presents an 18.5–20.6 GHz voltage-controlled oscillator (VCO) that achieves a wide tuning range and low phase noise, suitable for frequency-modulated continuous-wave (FMCW) radar systems. The VCO’s resonator consists of a transformer in which the primary attaches to the core, the secondary attaches to a varactor bank with the center tap providing one polarity of the tuning voltage, and a capacitor shorts the primary to the secondary for AC signals. Compared to capacitive-coupled varactors with resistive chokes, this AC-shorted transformer tank permits larger varactors without an associated noise penalty. This work analyzes the capacitive and inductive coupling to find their optimal values. A Colpitts VCO is implemented in 130 nm SiGe BiCMOS to illustrate the achievable wideband and low-noise performance. The circuit has a phase noise of −112 dBc/Hz at 1 MHz offset across a continuous tuning range of 10.4%. When used with two frequency doublers within a 76–81 GHz FMCW automotive radar transceiver, the local oscillator can fulfill both the phase noise requirement of long-range radar and the tuning range requirement of short-range radar applications in a single circuit.